Proyecto de factibilidad para la apertura de una agencia de la cooperativa de ahorro y crédito campesina Coopac Ltda., en la ciudad de Loja. - Armijos Ordóñez, Valeria del Pilar (2011)
The feasibility project for the implementation of an AGENCY SAVINGS AND CREDIT COOPERATIVE RURAL COOPAC IN THE CITY OF LOJA, we performed based on the applicants' applications also due to the small business sector currently lacks low-interest financial offers that impeded socio-economic development of the association. This paper hopes to give the technical support of this proposal and for this study were part of the following: Originally conducted a market test, to thus determine the conditions which are at the level of income and savings capacity to justify the implementation of the Agency. Proposal starts with market research, which was a key tool for a clear optical development of the market and knows the aspects of supply and demand and other issues that were vital to determine the implementation of the agency. As a second step, the technical study prepared which details issues related to the size and location of the Agency COOPAC, it is noteworthy that when an entity that supports micro business sector is necessary that the location is in a predominantly commercial, which is chosen Cuarto Centenario sector, specifically in the streets Lauro Guerrero and Miguel Riofrío corner. Also in this section is given to know the different physical requirements of both technology and most importantly the human talent that is required for operation. Then in the third point was elaborated Legal management study, which includes everything related to the agency's administrative, legal provisions, both functional and structural charts of the Matrix and the Agency. Another important factor is that this section refers to the profile of staff working in the Agency. Universidad Nacional de Loja. Área Jurídica Social y Administrativa. In the fourth point of the study Financial, which served to determine the monetary value that is needed to start the project value is $ 127,068.65 (One hundred twenty-seven thousand and sixty-eight with 65/100 Dollars), likewise described where the funds come from to finance them, not forgetting the amount of income generated by the project and costs for the service. After obtaining this information we proceeded to projecting the number of years of the project (4 years), been based on the annual inflation rate. (3.57%) As a final stage of the project is the financial assessment to find indicators to decide on the feasibility of implementing the COOPAC, it performed the calculations for the (NPV) Net Present Value, the same amount to $ 24300.12 (Twenty four thousand three hundred thirty-two with 94/100 Dollars), (IRR) Internal Rate of Return is 24.94%, THE COST BENEFIT equals $ 0.64 cents on the dollar and the recovery period is 4 years CAPITAL 18 months. All these indicators were vital to determine whether it is feasible to implement the COOPAC Agency